2021
DOI: 10.1021/acs.energyfuels.1c00965
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Feedstock Properties on the Deactivation of a Vacuum Gas Oil Hydrocracking Catalyst

Abstract: The aim of this study was to understand the impact of vacuum gas oil (VGO) properties on the deactivation rate of a hydrocracking catalyst (nickel− molybdenum sulfide dispersed on a carrier containing USY zeolite). For this purpose, two hydrotreated feeds of different densities, organic nitrogen (∼120−150 ppmw) and aromatic content, were hydrocracked under operating conditions that favor catalyst deactivation, that is, high temperature (T = 418 °C) and high space velocity (LHSV = 3 h −1 ). The catalyst perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…Since no meaningful differences were observed in sintering or depromotion between the spent samples (Supporting Information Table S1, TEM analysis), this behavior was attributed to a higher coke buildup with the reference catalyst. In ref , we had already observed a strong correlation between the amount of coke formation and the loss of hydrogenation activity. The coke deposition is determined by the metal/acid (M/A) balance.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Since no meaningful differences were observed in sintering or depromotion between the spent samples (Supporting Information Table S1, TEM analysis), this behavior was attributed to a higher coke buildup with the reference catalyst. In ref , we had already observed a strong correlation between the amount of coke formation and the loss of hydrogenation activity. The coke deposition is determined by the metal/acid (M/A) balance.…”
Section: Discussionmentioning
confidence: 74%
“…It seems that the nitrogen in the coke is the main cause of the decrease in residual cracking activity. We had already pointed out in our previous work that the residual acidity of the catalyst was decorrelated from the total coke content and specifically related to nitrogen compounds.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The coke content of the catalyst gradually increased with depth in the catalyst bed, as hydrogen has been consumed by the reaction resulting in lower hydrogen pressure at the bottom of the catalyst bed 5) . Feed content of nitrogen and aromatic com- pounds also affects the amount of hydrogen consumption 17) . Experiments with different operating conditions such as reaction temperature or hydrogen pressure and measurement of the coke precursor asphaltene removal ratio indicated that effective utilization of limited hydrogen contributed to coke suppression 21) .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, to obtain a pure bifunctional behavior, these functions must be well-balanced to provide an appropriate cracking/hydrogenation balance [19,20]. The composition of the catalysts has been tuned to maximize the formation of fractions with commercial interest, such as naphtha and diesel, from secondary refinery streams like VGO (vacuum gasoil) [21,22]. However, for hydrocracking neat plastics or plastics blended with secondary refinery streams it is necessary to develop new catalysts specifically designed for this purpose.…”
Section: Introductionmentioning
confidence: 99%